Thursday

March 26, 2015

March 26, 2015

Posted by **Robin** on Monday, July 15, 2013 at 8:49am.

f(x)=(8)/(x^2)−(8)/(x^5)

.

Let F(x) be the antiderivative of f(x) with F(1)=0.

Then F(2) equals ?

- Calculus -
**Steve**, Monday, July 15, 2013 at 10:11amF = ∫ 8/x^2 - 8/x^5 dx

= 8/3 x^3 - 8/6 x^6 + C

Since F(1) = 0,

8/3 x^3 - 4/3 x^6 + C = 0

C = 4/3 - 8/3 = -4/3

F(x) = 8/3 x^3 - 4/3 x^6 - 4/3

F(2) = 8/3 (8) - 4/3 (64) = -64

**Answer this Question**

**Related Questions**

Calculus - Consider the function f(x)=(7/x^2)-(6/x^6). Let F(x) be the ...

calculus - 7) Consider the function f(x)=(10/x^2)−(2/x^6). Let F(x) be ...

Calculus I - Consider the function f(x)=((2)/(x^2))-((3)/(x^5)). Let F(x) be the...

Calculus - Find f(x) if f′(x)=(−3)⋅x+(−1) and f(−4...

Calculus - Consider the function f(x)=x^4 + 8sqrtx Let F(x) be the ...

math - Consider the function f(t)=2sec^2(t)–6t^2 . Let F(t) be the ...

Calculus (Antiderivatives) - Suppose f(x) is a continuous function. Then a ...

Calculus - Consider the function f(x)=4(x−3^2/3. For this function there ...

Calculus Help and Check - 1)Find the most general antiderivative of the function...

Calculus - The marginal revenue for x items in dollars is given by R′(x...